A review of transition experiences in perinatally and behaviourally acquired HIV‐1 infection; same, same but different?. (16th May 2017) - Lam, Phung Khanh; Fidler, Sarah; Foster, Caroline
Abstract: Introduction: Despite sharing common psychosocial and developmental experiences, adolescents living with perinatally and behaviourally acquired HIV‐1 infection are different in terms of timing of HIV infection and developmental stage at infection. Therefore, it is of interest to identify similarities and differences between these two groups of adolescents living with HIV in their experiences, facilitators and barriers during the transition process. Methods: A detailed literature search of peer‐reviewed published papers was conducted on PubMed to identify relevant original research or viewpoints published up to September 2016. Conference abstracts and other unpublished data sources were not included. Results: Existing published literature, mainly using qualitative methods, explores the transition from paediatric to adult healthcare provision, as experienced by these two groups of young people. Reports highlight the variation and similarities in their experiences and challenges of transition. Findings from the USA and Europe predominate, while experience from Africa and Asia is lacking, despite the importance of these regions in the global epidemic. Conclusions: Published transition data remain limited, and there are few studies focusing on behaviourally infected adolescents and key population groups (e.g. adolescents who use drugs, lesbian/gay/transgender individuals). Robust definitions of the transition process and standardized outcome measures are required to facilitate cross‐study and geographic comparisons.